Sinus lifting dengan teknik lateral window dan transalveolar osteotomy Lateral window and transalveolar osteotomy sinus lifting technique - Muhammad Ruslin (Journal of Dentomaxillofacial Science, 2011)
The insertion of dental implants in atrophy maxilla is a complicated issue because no bone support due to expansionof maxillary sinus and atrophy of maxillary ridge alveolar. Surgery by sinus lifting with autogenous bonetransplantation has been proven to be an acceptable treatment to get bone support. The lateral window techniqueand transalveolar osteotomy sinus lifting are the methods to correct the height of inadequate bone in the posteriorarea of maxilla for preparation of implan dental insertion. Technique of transalveolar osteotomy sinus lifting isnoninvasive compared to lateral window sinus lifting technique.